2021
DOI: 10.3390/ma14216699
|View full text |Cite
|
Sign up to set email alerts
|

Strain Compensation and Trade-Off Design Result in Exciton Emission at 306 nm from AlGaN LEDs at Temperatures up to 368 K

Abstract: In this study, we suppressed the parasitic emission caused by electron overflow found in typical ultraviolet B (UVB) and ultraviolet C (UVC) light-emitting diodes (LEDs). The modulation of the p-layer structure and aluminum composition as well as a trade-off in the structure to ensure strain compensation allowed us to increase the p-AlGaN doping efficiency and hole numbers in the p-neutral region. This approach led to greater matching of the electron and hole numbers in the UVB and UVC emission quantum wells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The biggest challenge when fabricating AlGaN-based UVB LEDs is the low doping efficiency of the p-AlGaN layer at high Al contents. Thus, we have previously suggested that one of the main reasons for the J-droop in AlGaN-based UVB LEDs is the insufficient conductivity of the neutral region of the p-AlGaN layers, with the number of holes injected into the MQWs resulting in a mismatch of the quasi-charge-neutral conditions [ 37 ]. To overcome the efficiency droop at a higher current density (>100 A cm –2 ), it is necessary to a subtly design the p-layer to improve the hole injection efficiency and the uniformity of the hole concentration within the well region of the MQWs, thereby avoiding Auger recombination as a result of a mismatch in the hole and electron concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest challenge when fabricating AlGaN-based UVB LEDs is the low doping efficiency of the p-AlGaN layer at high Al contents. Thus, we have previously suggested that one of the main reasons for the J-droop in AlGaN-based UVB LEDs is the insufficient conductivity of the neutral region of the p-AlGaN layers, with the number of holes injected into the MQWs resulting in a mismatch of the quasi-charge-neutral conditions [ 37 ]. To overcome the efficiency droop at a higher current density (>100 A cm –2 ), it is necessary to a subtly design the p-layer to improve the hole injection efficiency and the uniformity of the hole concentration within the well region of the MQWs, thereby avoiding Auger recombination as a result of a mismatch in the hole and electron concentrations.…”
Section: Introductionmentioning
confidence: 99%